Peran Jaksa Penuntut Umum Dalam Pembuktian Unsur Kelalaian Pada Tindak Pidana Yang Mengakibatkan Kematian (Studi Kasus Putusan Nomor 147/PID.B/2022/PN MGT) - Annashrul, Fajar Luthfi; Apriyani, Maria Novita (Lex Stricta : Jurnal Ilmu Hukum, 2026)
The Attorney General’s Office of the Republic of Indonesia plays a central role in the criminal justice system, with public prosecutors responsible for ensuring that every case is handled professionally, effectively, and fairly. In the field of traffic safety, accidents caused by driver negligence often result in injury or death to victims. Driver negligence resulting in death is regulated under Article 310(4) of Law No. 22 of 2009, carrying a potential prison sentence of up to six years. The complexity of negligence cases requires Public Prosecutors to prove a clear causal relationship between the defendant’s negligence and the injuries sustained by the victim. This study aims to analyze the parameters of the causal relationship in criminal negligence cases resulting in injuries. It employs an empirical legal approach using case studies of the relevant court decisions. Primary data was obtained through interviews with public prosecutors handling the cases, while secondary data was derived from related legal documents.